INTRANASAL INHALATIONS OF BIOACTIVE FACTORS PRODUCED BY M2 MACROPHAGES IN THE TREATMENT OF PATIENTS WITH ORGANIC BRAIN SYNDROME - A. A. Ostanin (SPb RAACI, 2018)
The aim of present study was to evaluate safety and clinical efficacy of inhalatory immunotherapy based on intranasal delivery of bioactive factors produced by M2 macrophages applied for treatment of patients with organic brain syndrome (OBS).Materials and methods. The study under the NCT02957123 protocol (www.ClinicalTrails.gov) included thirty patients with OBS of various genesis (10 men and 20 women aged 18 to 81; Me, 62.5 years). Neurological assessment and the levels of 32 cytokines in the blood serum of patients were evaluated before and 2-3 days after completion of inhalation immunotherapy.Intranasal inhalations of cell-free culture medium of M2 macrophages (2 mL, once a day for 28-30 days) were safe and well tolerated. None of 30 treated patients had severe adverse events and serious treatmentrelated side reactions. One month after starting the inhalations, a positive dynamics in neurological status was noted in all the patients. A marked clinical response was documented in twenty out of thirty patients (67%), which manifested as improvement, according to all scales and questionnaires. The neurological improvement was not reversed over 6 months of follow-up period. In other ten patients (33%), a moderate clinical response was shown as improvement of individual scores. The positive changes were as follows: 1) a 43% decrease in anxiety and depression scores (according to HADS scale, pU = 0.0008); 2) an increase of total motor activity (stability and gait) by 25%, pU = 0.0001); 3) correction of cognitive functions (MoCa test, pU = 0.007); 4) reduced number and intensity of the disease symptoms by 52% (pU = 0.0001). This marked clinical response to immunotherapy is shown to be associated with correction/normalization of serum hepatocyte growth factor (HGF) level.Conclusion. Inhalation immunotherapy based on intranasal delivery of bioactive factors produced by M2 macrophages can improve neurological and functional recovery in patients with organic brain syndrome.